2012
DOI: 10.5380/avs.v17i1.21446
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and humidity in the Brazilian tropical summer affecting the in vivo embryo production of Nelore breed in superovulation program

Abstract: This study used Nelore embryo donors to evaluate the effects of summer temperatures and humidity in a tropical area on embryo recovery. Seventeen cows were randomly assigned to three groups (G1, G2 and G3) as well as 28 heifers into four groups (G4, G5, G6 and G7), and underwent a consecutive 4 d superovulation protocol (Day 0 to 3) and two artificial inseminations (AI; Day 4 and 5). Cortisol concentrations were determined on Day 0, 4 and 5. Temperature and humidity index (THI) was recorded from Days 0 to 7. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…When the ambient temperature reaches critical temperatures higher than TCZ, the efficiency of the heat loss processes is reduced and the animal enters heat stress (HS) (Silanikove 2000), which leads to a consequent activation of thermoregulation mechanisms (Rodrigues et al 2010). As responses, changes in animal behavior, body temperature, respiratory frequency, heart frequency, and sweating rate (Paranhos da Costa 2004), as well as alterations in adrenal activity and immune response, are observed (Geraldo et al 2012), Macedo and Zúccari 2012). Reduction of weight gain (Navarini et al 2009), food consumption (Geraldo et al 2012), and consequently a reduction on reproductive performance has also been reported (Lima et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…When the ambient temperature reaches critical temperatures higher than TCZ, the efficiency of the heat loss processes is reduced and the animal enters heat stress (HS) (Silanikove 2000), which leads to a consequent activation of thermoregulation mechanisms (Rodrigues et al 2010). As responses, changes in animal behavior, body temperature, respiratory frequency, heart frequency, and sweating rate (Paranhos da Costa 2004), as well as alterations in adrenal activity and immune response, are observed (Geraldo et al 2012), Macedo and Zúccari 2012). Reduction of weight gain (Navarini et al 2009), food consumption (Geraldo et al 2012), and consequently a reduction on reproductive performance has also been reported (Lima et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to Silanikone (2000), when the environmental temperature exceeds the ZCT the thermolysis mechanisms are reduced and the animal goes into heat stress and this leads to a consequent inactivation of thermoregulatory processes (RODRIGUES et al, 2010). As a response to heat stress, changes in the animal's behavior, body temperature, respiratory rate, as well as changes in the activity of the autonomous nervous system and immunity of the animals will be observed (PARANHOS DA COSTA 2004;GERALDO et al 2012;MACEDO;ZÚCCARI 2012).…”
Section: Introductionmentioning
confidence: 99%